Trends in disability and program participation among U.S. veterans. Issue 3 (July 2016) - Ben-Shalom, Yonatan; Tennant, Jennifer R.; Stapleton, David C.
Abstract: Background: Disability is increasingly part of the lives of veterans and more research is needed to understand its impact on veterans' participation in disability benefit programs. Objective/hypothesis: We examine how recent trends in receipt of service-connected disability compensation from the Department of Veterans Affairs (VA) compare to trends in self-reported disability and participation in Social Security Disability Insurance (DI) and Supplemental Security Income (SSI) among veterans. Methods: We use 2002–2013 data from the Current Population Survey to describe trends in receipt of VA disability compensation and to compare between trends in self-reported disability and DI/SSI participation for veterans versus nonveterans. Results: The percentage of veterans reporting they receive VA disability compensation increased substantially from 2002 to 2013 and was especially notable among younger (ages 18–39) and older (ages 50–64) veterans. From 2009 to 2013, self-reported disability increased among the younger and older veterans but not among middle-age veterans and nonveterans, and self-reported cognitive disability increased substantially among young veterans. DI/SSI participation among older veterans increased more than for nonveterans over the period examined. Conclusions: Effective policies are needed to incentivize work among young veterans and to help them obtain both the skills they need to succeed in the labor force and the supports (such as psychiatric health services) they need to do so. Older veterans are facing increasing challenges in the labor market, and further research is needed to determine whether these challenges are primarily related to health, a growing skills gap, or poorly-aligned incentives.